Association of NTDs with maternal and only mother serum vitamin B12 Association-A Review Study - Fakhrul Amin Badal; Ferdous Jahan Binte Rashid; Rehena Parvin; Nisfun Naher; Marzia Khanam (Pediatric Review: International Journal of Pediatric Research, 2024)
Neural tube defects (NTDs) are one of the commonest birth defects in our clinical practices. Maternal nutritional factors are associated with increased chance of development of NTDs in offspring. Periconceptional folic acid supplementation can prevent up to three fourths of neural tube defects (NTDs). Some studies reported that there might be an association between maternal serum vitamin B12 levels and NTDs. Dietary vitamin B12 deficiency is a common problem in the Indian subcontinent including Bangladesh because of inadequate dietary intake, dietary habit and/or malabsorption. There is scarcity of study to establish relationship of vitamin B12 and NTDs.  It would be beneficial to see the association of vitamin B12 and NTDs in a Bangladeshi population, which may help in deciding about vitamin B12 supplementation as a preventive measure of NTDs.